Child protection using research to improve policy and practice - Haskins, Ron.; Webb, Mary Bruce; Wulczyn, Fred.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2007)
"Reports the results of the National Survey of Child and Adolescent Well-Being. Discusses implications and suggests alternatives for types of personal and familial problems the programs are meant to address, the range of services and interventions that the child protection system can make available, and an assessment of these programs"--Provided by publisher.
Using high-quality research to improve child protection practice : an overview / Ron Haskins, Fred Wulczyn, and Mary Bruce Webb -- Identifying young maltreated children with developmental delays / Steven A. Rosenberg, Elliott G. Smith, and Arnold Levinson -- Intimate partner violence in the child welfare system : findings from the National Survey of Child and Adolescent Well-being / Andrea L. Hazen ... [et al.] -- Initial construction of an actuarial risk assessment measure using the National Survey of Child and Adolescent Well-being / Aron Shlonsky -- Building on strengths : current status and opportunities for improvement of parent training for families in child welfare / Michael S. Hurlburt ... [et al.] -- Alcohol, drug, and mental health service need for caregivers and children involved with child welfare / Anne M. Libby ... [et al.] -- Medicaid and mental health care for children in the child welfare system / Ramesh Raghavan and Arleen Leibowitz -- Systems integration and access to mental health care / John A. Landsverk, Michael S. Hurlburt, and Laurel K. Leslie -- Predictors of reunification / Judith Wildfire, Richard P. Barth, and Rebecca L. Green -- Placement stability and early behavioral outcomes among children in out-of-home care / David M. Rubin ... [et al.] -- Kinship care and nonkinship foster care : informing the new debate / Richard P. Barth ... [et al.] -- Child maltreatment recurrence among children remaining in-home : predictors of re-reports / Patricia L. Kohl and Richard P. Barth -- Physical abuse and adolescent development / John Eckenrode, Charles Izzo, and Elliott G. Smith -- Addressing the educational needs of children in child welfare services / Mary Bruce Webb ... [et al.].
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Abused children -- Services for -- United States; Child welfare -- United States; Dysfunctional families -- Services for -- United States; Family services -- United States; Foster children -- Services for -- United States; Electronic books